Nieustalona laminarna konwekcja swobodna na pionowej płaskiej płycie - Pop, I. (Engineering Transactions, 1969)
In the present work we shall consider the unsteady laminar free-convection caused by heating a semi-finite flat vertical plate of length l. The analytical solution in closed form for the distribution of velocity and temperature has been obtained for abrupt changes of the surface temperature and the Prandtl number equal to unity. Those expressions have been obtained by expansion of the sought functions into finite series. Numerical results have been obtained for the the Nusselt number and surface friction for various values of time. The results are also presented graphically.